A dual-risk model of user adoption of mobile-based smoking cessation support services. Issue 7 (2nd July 2016) - Cocosila, Mihail; Turel, Ofir
Abstract : This study proposes and validates a dual-risk model of the drivers and inhibitors of the adoption of a mobile e-health application for smoking cessation. This model extends existing approaches for risk taking by accounting for two opposite types of risk: the risk of using the mobile service and risks of not using it, both of which are argued to be instrumental to user decision to use healthcare support technologies. The proposed model was estimated with data collected from 422 smokers and mobile phone users in the UK and Canada. The findings suggest that adoption decisions regarding such a mobile service are driven by intrinsic and extrinsic motivations which channel the effects of the above-mentioned risk assessments on use intentions. This implies that to increase the success of mobile phone use in smoking cessation programmes, perceptions regarding both risks could be targeted.